(untitled) (American Journal of Islam and Society, 2002)
This paper compares the Islamic and the western social scientific perspectives on corruption. Jt is argued that the emerging shift in social scientific thought in viewing corruption from "grease that oils the economic wheel" to a "menace that undermines economic growth" has brought rational understanding of the phenomenon much closer to [slamic doctrine. Where they differ is with respect to remedial action. The western approach focuses on governance and designing appropriate systems and institutions that gear information and incentives toward minimizing opportunities and enticement for corruption. In short, it emphasizes constraints external to the individual. By comparison, Islam seeks to go beyond such constraints, and also instill in believers a clear "second-order" preference for noncorrupt behavior. lt recommends developing a firm belief in transcendent accountability, stresses character building through practicing moral virtues and shunning vices. In essence, much of the restraint comes from within through a moral renovation. rt is our contention that both emphases are important in eliminating corruption and that the followers oflslam and the West can learn from one another.